PENGARUH BRAND EQUITY DAN TRUST TERHADAP BRAND LOYALTY CUSTOMER SATISFACTION SEBAGAI VARIABEL MEDIASI PADA PT. SORAYA BEDSHEET KOTA PADANG - Pamija, Atha Razin; Asria, Maya (STKIP Pesisir Selatan, 2026)
This study aims to analyze the influence of brand equity and trust on brand loyalty with customer satisfaction as a mediating variable for customers of PT. Soraya Bedsheet, Padang City. The study used a quantitative approach with a causality design. Data were collected through questionnaires distributed to 102 respondents selected using a purposive sampling technique, namely consumers who had purchased the product at least twice. Data analysis was conducted using the Partial Least Square–Structural Equation Modeling (PLS-SEM) method. The results showed that brand equity and trust had a positive and significant effect on customer satisfaction and brand loyalty. Customer satisfaction was also proven to have a positive effect on brand loyalty and acted as a mediating variable in the relationship between brand equity and trust on brand loyalty. These findings indicate that customer loyalty will be formed more strongly if the perception of brand value and the level of consumer trust are accompanied by a high level of satisfaction experience. This study provides practical implications for companies to strengthen brand management strategies and customer relationships to create sustainable loyalty, as well as contributing theoretically to the development of marketing studies related to the formation of brand loyalty.